Integração entre escola e família no componente curricular de ciências: práticas pedagógicas desenvolvidas no 6º ano da escola básica no município de Cametá-PA - CARDOSO, Rodrigo de Oliveira (2024)
The present work presents an investigation and reflections on the Integration between School and Family in the Discipline of Sciences: Pedagogical Practices developed in the 6th Year of the Basic School in the Municipality of Cametá-PA, from the understanding of the importance of families for the educational and children's school and the integration of families with the school to overcome the learning difficulties presented by the students inside the classroom, seeking to understand how the family relationships developed in a troubled way can be related to these difficulties of the students. the research was developed in the city of Cametá-Pa, at Municipal elementary school teacher Maria Nadir Filgueira Valente through a dialogue conversation with the management and teaching of the school, being guided by a semi structured interview, following as support literatures that deal with the themes of the school. importance of families in educational and school processes, learning difficulties, relationships between family and school. Thus, with the research, we sought to contribute significantly to the teaching and learning processes, showing the importance of families' participation in children's social and school life, which proved through the results to be a preponderant factor for the development of children. students within the school, helping to overcome difficulties.